Fractais na formação de professores: um estudo interdisciplinar no curso de licenciatura em matemática da universidade do estado do rio grande do norte - Oliveira, Paula Roberta Mendes de (2020)
This work aims to understand the potential of Fractal Geometry as a didactic-methodological interdisciplinary proposal in the formation of the Mathematics teacher from discussions with undergraduate students in Mathematics, that also will be the future actors responsible for this process. For this, we conducted an exploratory qualitative research with some characteristics of action research with a group of students from the discipline of Laboratory of Teaching-Learning Practice in Mathematics II of the 5th period of the Mathematics Degree course at the Universidade do Estado do Rio Grande do Norte (Rio Grande do Norte State University), Central Campus. Thus, it brings, as a result, the view of the graduates on the presented didactic materials that is based on the Geometry Fractal for the teaching of mathematics, which was developed together with the Theory of Chaos, something new, differentiated for the graduates and intimately recommended to interdisciplinarity. In addition, we realized a state of knowledge about the approach of this new geometry, its relationship with interdisciplinarity and the formation of the mathematics teacher, dissertations and theses of the Catalog of theses and dissertations of the covers in the period from 2005 to June 2017. Then, we concluded that a didactic-methodological proposal offers a desirable potential and its use can contribute to facilitate the teaching and learning process at all levels, since it improves each of them, from Basic Education to Higher Education, although there are still interdisciplinary gaps, which generates new paths to be taken by teachers who like and are always looking for new possibilities to improve their practice in the classroom